2006
DOI: 10.1159/000096455
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Transport Systems of<i> Bifidobacterium longum </i>NCC2705

Abstract: Here we present the complement of the carbohydrate uptake systems of the strictly anaerobic probiotic Bifidobacterium longum NCC2705. The genome analysis of this bacterium predicts that it has 19 permeases for the uptake of diverse carbohydrates. The majority belongs to the ATP-binding cassette transporter family with 13 systems identified. Among them are permeases for lactose, maltose, raffinose, and fructooligosaccharides, a commonly used prebiotic additive. We found genes that encode a complete phosphotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
103
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 54 publications
8
103
1
Order By: Relevance
“…B. longum JCM 1217 encodes a number of candidates for the ␣-L-arabinofuranosidase gene, 11 members of the GH43 gene family, and 4 members of the GH51 gene family. Several reports indicate that B. longum has the ability to grow on L-arabinose and ␣-L-arabinooligosaccharides (14,23,(25)(26)(27). We showed that B. longum also uses ␤-Ara 2 as a carbohydrate source (supplemental Table S4).…”
Section: Discussionmentioning
confidence: 56%
“…B. longum JCM 1217 encodes a number of candidates for the ␣-L-arabinofuranosidase gene, 11 members of the GH43 gene family, and 4 members of the GH51 gene family. Several reports indicate that B. longum has the ability to grow on L-arabinose and ␣-L-arabinooligosaccharides (14,23,(25)(26)(27). We showed that B. longum also uses ␤-Ara 2 as a carbohydrate source (supplemental Table S4).…”
Section: Discussionmentioning
confidence: 56%
“…Lactose is preferred over glucose by B. longum subsp. longum NCC2705, as suggested by transcriptional repression of glpP, a glucose uptake gene (Parche et al, 2007). As a disaccharide, lactose provides glucose for glycolysis as well as galactose that can be shunted directly to the Leloir pathway for sugar nucleotide biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are at least three permease systems in B. longum subsp. longum NCC2705 that are active for lactose uptake, while glucose is transported by two systems, of which the phosphotransferase is transcribed at a low level (Parche et al, 2007). In order to determine whether the differences in EPS production between cultures of B. longum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the K d value for LNT was much larger, being 11 M. Therefore, we conclude that BL1638 -1640 is an ABC transporter specific for disaccharides GNB and LNB. Although this operon lacks a nucleotide-binding domain, it is likely that a universal nucleotide-binding domain (BL0673) energizes the sugar-transporting system (21). Colonization of adult human intestine by Bifidobacteria is thought to involve the recognition and metabolism of mucin glycans (72,73).…”
Section: Analysis Of Ligand Specificity By Itc-mentioning
confidence: 99%
“…BL1638 is also thought to be a membrane-anchored lipoprotein, because its primary structure contains a lipid-anchor signal sequence, GLAGCG. In the genome of B. longum NCC2705, there are 13 putative ABC transporter systems for the uptake of sugars (21). However, there are no reports on the three-dimensional structures of sugar transporters from Bifidobacteria and their substrate recognition mechanisms.…”
mentioning
confidence: 99%